A synthesis and meta-analysis of the relationship between trait self-control and healthier practices in physical activity, eating, and sleep domains. (April 2023) - Andrade, Fernanda C.; Hoyle, Rick H.
Abstract: This paper updates and extends prior work by meta-analyzing the fast-growing literature on the association between individual differences in trait self-control and multiple outcomes within the domains of physical activity, eating, and sleep. Random-effects models with nesting by study and sample were estimated for the aggregate association between self-control and all health-related domains, for each domain independently, and for moderated meta-regressions testing whether effect sizes varied by method, measurement, and sampling within each domain. Self-control was modestly associated with engagement in health-related activities, with significantly stronger associations for sleep relative to eating and physical activity-related outcomes. Within eating and sleep domains, associations significantly varied as a function of outcome type and whether they were assessed in terms of health-promotion or health-risk practices. Findings suggest that the upper bound of what can be predicted by individual differences in self-control varies by health-related outcome. Importantly, smaller associations point to the potential role of other individual differences, contextual affordances, and biological factors in explaining healthier physical activity, eating, and sleep-related practices. The granular approach taken in this investigation may ultimately aid the translation of a growing literature on the role of individual differences in self-control into effective health behavior maintenance and change interventions. Highlights: Interest in self-control and health has sharply increased in the last decade. This multivariate meta-analysis synthesized evidence from 107 studies, N = 72, 883. Good self-control is associated with healthier physical activity, eating, and sleep. Self-control is more strongly associated with directly modifiable practices. Self-control overlaps more strongly with less risky, than with healthier, lifestyles.